Evaluating Patient-Centered Outcomes in Clinical Trials of Procedural Sedation, Part 2 Safety: Sedation Consortium on Endpoints and Procedures for Treatment, Education, and Research Recommendations. (November 2018) - Ward, Denham S.; Williams, Mark R.; Berkenbosch, John W.; Bhatt, Maala; Carlson, Douglas; Chappell, Phillip; Clark, Randall M.; Constant, Isabelle; Conway, Aaron; Cravero, Joseph; Dahan, Albert; Dexter, Franklin; et al.
Abstract : The Sedation Consortium on Endpoints and Procedures for Treatment, Education, and Research, established by the Analgesic, Anesthetic, and Addiction Clinical Trial Translations, Innovations, Opportunities, and Networks, a public–private partnership with the US Food and Drug Administration, convened a second meeting of sedation experts from a variety of clinical specialties and research backgrounds to develop recommendations for procedural sedation research. The previous meeting addressed efficacy and patient- and/or family-centered outcomes. This meeting addressed issues of safety, which was defined as "the avoidance of physical or psychological harm." A literature review identified 133 articles addressing safety measures in procedural sedation clinical trials. After basic reporting of vital signs, the most commonly measured safety parameter was oxygen saturation. Adverse events were inconsistently defined throughout the studies. Only 6 of the 133 studies used a previously validated measure of safety. The meeting identified methodological problems associated with measuring infrequent adverse events. With a consensus discussion, a set of core and supplemental measures were recommended to code for safety in future procedural clinical trials. When adopted, these measures should improve the integration of safety data across studies and facilitate comparisons in systematic reviews and meta-analyses.